2009
DOI: 10.1254/jphs.08r18fm
|View full text |Cite
|
Sign up to set email alerts
|

New Topics in Vasopressin Receptors and Approach to Novel Drugs: Vasopressin and Pain Perception

Abstract: Abstract. Arginine vasopressin (AVP) activates three vasopressin receptors and it also has an agonistic activity on the oxytocin receptor. For an accurate description of the target receptor subtype(s) responsible for complex AVP and oxytocin actions, a careful evaluation of ligand specificity and receptor activities are required, particularly when these receptors are co-expressed in the central nervous system. Previous studies suggest that AVP plays a regulatory role in nociception through the direct activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
(46 reference statements)
1
27
0
1
Order By: Relevance
“…A number of studies have reported on the analgesic actions of exogenously administered neurohypophysial hormones against different pain modalities (Lundeberg et al, 1994; Ge et al, 2002; Yu et al, 2003; Gao and Yu, 2004; Koshimizu and Tsujimoto, 2009), but little is known about the role of endogenous OXT and AVP in pain processing. The anatomical distribution of OXT and OTRs in rat strongly supports such a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have reported on the analgesic actions of exogenously administered neurohypophysial hormones against different pain modalities (Lundeberg et al, 1994; Ge et al, 2002; Yu et al, 2003; Gao and Yu, 2004; Koshimizu and Tsujimoto, 2009), but little is known about the role of endogenous OXT and AVP in pain processing. The anatomical distribution of OXT and OTRs in rat strongly supports such a role.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the actions of OXT and AVP in the CNS have received increasing attention because of the documented role of these peptides in the regulation of complex social and sexual behavior in mammals (Donaldson and Young, 2008; Young et al, 2008), including humans (Baumgartner et al, 2008; Petrovic et al, 2008; Walum et al, 2008). Concomitantly, a growing literature has demonstrated the analgesic effects of OXT and AVP in both human and rodent species (Honda and Takano, 2009; Koshimizu and Tsujimoto, 2009). Indeed, OXT was reported to be analgesic in a variety of pain tests when administered into the brain (Ge et al, 2002; Lund et al, 2002; Wang et al, 2003; Gao and Yu, 2004), the spinal cord (Yu et al, 2003; Miranda-Cardenas et al, 2006; Condes-Lara et al, 2007) or systemically (Lundeberg et al, 1994; Reeta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that AVP causes antinociception in both humans and animals [2,11]. The antinociceptive activity was observed after subcutaneous, intraperitoneal or intracerebroventricular administration of AVP [3,14]. In contrast, Brattleboro rats, which are naturally deficient in AVP, had a hyperalgesic state in flinch-jump threshold test and impaired stress analgesia [4].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Vasopressin stimulates the secretion of β-endorphins by the hypothalamus, which could cause a central analgesic effect. 20,21 …”
Section: Discussionmentioning
confidence: 99%